Neutrophil Gelatinase-Associated Lipocalin: A New Marker of Renal Function in C-Related End Stage Liver Disease - Omkolsoum Mohamed Alhaddad; Ayman Alsebaey; Mohamed Omar Amer; Hala Hany El-Said; Tary Abdel Hamid Salman (Gastroenterology Research and Practice)
Background/Aims. Renal impairment is a common complication of cirrhosis. Serum creatinine is less sensitive in these patients. Measurement of the glomerular filtration rate (GFR) is the gold standard but time consuming. The aim is to validate plasma NGAL (pNGAL) and urinary NGAL (uNGAL) as markers of renal function in patients with HCV related cirrhosis. Patient and Methods. One hundred HCV related end stage liver cirrhosis patients were randomized into two groups: Group I (n=35), patients with GFR < 60 mL/m measured by isotope scanning of the kidney (Renogram), and Group II (n=65), patients with GFR ≥ 60 mL/m. The pNGAL and uNGAL were measured within 2 days of the Renogram. Results. Both groups were matched with age, sex, and Child Pugh score. There was statistically significant difference between both groups regarding serum creatinine (1.98 ± 1.04 versus 1.38 ± 0.88 mg/dL; p=0.003) and pNGAL level (5.79 ± 2.06 versus 7.25 ± 3.30 ng/dL; p=0.019). Both groups were comparable (p>0.05) for the uNGAL (6.00 ± 0.78 versus 6.03 ± 0.96 ng/mL). Unlike uNGAL, the pNGAL positively correlated with total GFR by Renogram (r=0.3; p=0.001). With a cutoff ≥4 ng/mL, pNGAL had 94.3% sensitivity and 1.5% specificity and PPV = 34, NPV = 33.3, LR+ = −175.1, and LR− = −60.6. Conclusion. The pNGAL is a promising marker of the renal function in patients with cirrhosis.